Leaf δ15N as a physiological indicator of the responsiveness of N2-fixing alfalfa plants to elevated [CO2], temperature and low water availability - Ariz, Idoia; Cruz, Cristina; Neves, Tome; Irigoyen, Juan J.; García, Carmen; Nogués, Salvador; Aparicio-Tejo, Pedro M.; Aranjuelo, Iker (Frontiers in Plant Science, 2015)
The natural 15N/14N isotope composition (δ15N) of a tissue is a consequence of its N source and N physiological mechanisms in response to the environment. It could potentially be used as a tracer of N metabolism in plants under changing environmental conditions, where primary N metabolism may be complex, and losses and gains of N fluctuate over time. In order to test the utility of δ15N as an indicator of plant N status in N2-fixing plants grown under various environmental conditions, alfalfa (Medicago sativa L.) plants were subjected to distinct conditions of [CO2] (400 versus 700 mol mol-1), temperature (ambient versus ambient + 4ºC) and water availability (fully watered versus water deficiency - WD). As expected, increased [CO2] and temperature stimulated photosynthetic rates and plant growth, whereas these parameters were negatively affected by WD. The determination of δ15N in leaves, stems, roots and nodules showed that leaves were the most representative organs of the plant response to increased [CO2] and WD. Depletion of heavier N isotopes in plants grown under higher [CO2] and WD conditions reflected decreased transpiration rates, but could also be related to a higher N demand in leaves, as suggested by the decreased leaf N and total soluble protein (TSP) contents detected at 700 mol mol-1 [CO2] and WD conditions. In summary, leaf δ15N provides relevant information integrating parameters which condition plant responsiveness (e.g. photosynthesis, TSP, N demand and water transpiration) to environmental conditions.